(untitled) (Altre Modernità, 2016)
Against essentialist looks besieging the concept of political subject as an a priori, it is proposed here reflect on the dynamic and dialogic process of construction of the subject and the conditions required: the event, the construction of situations, the political drift, the desire of rebellion, and the production of knowledge, the creation of meaning. Education is a social field in constant dispute, at least in Europe for universal policies, in the nineteenth century, but the current extreme situation conflicting positions. Education -in Bourdieu’s notion of social space where agents equipped with different cultural capitals dispute its hegemony. Education can be a laboratory in which to test the possibilities and limits of public political project of citizenship, the project of the public sphere. I think that education can contribute, therefore, to the construction of the political subject if it facilitates the conceptual and procedural tools for policy learning reading of reality, to analyze what holds us to understand that we confers identity and subjectivity. Education will be truly educational if you feed the desire to walk and explore new possibilities of living in a dialogic understanding the differences; will be truly educational if active teaching strategies that allow the creation of life experiences based in the rebel gesture against all forms o control.